A truncated herpes simplex virus thymidine kinase phosphorylates thymidine and nucleoside analogs and does not cause sterility in transgenic mice. - Salomon, B (1995)
Dividing eukaryotic cells expressing the herpes simplex virus type 1 thymidine kinase (TK) gene are sensitive to the cytotoxic effect of nucleoside analogs such as acyclovir or ganciclovir (GCV). Transgenic mice with cell-targeted expression of this conditional toxin have been used to create animals with temporally controlled cell-specific ablation. In these animal models, which allow the study of the physiological importance of a cell type, males are sterile. In this study, we showed that this phenomenon is due to testis-specific high-level expression of short TK transcripts initiated mainly upstream of the second internal ATG of the TK gene. This expression is DNA methylation independent. To obtain a suicide gene that does not cause male infertility, we generated and analyzed the properties of a truncated TK (delta TK) lacking the sequences upstream of the second ATG. We showed that when expressed at sufficient levels, the functional properties of delta TK are similar to those of TK in terms of thymidine or GCV phosphorylation. This translated into a similar GCV-dependent toxicity for delta TK- or TK-expressing cells, both in vitro and in transgenic mice. However, delta TK behaved differently from TK in two ways. First, it did not cause sterility in delta TK transgenic males. Second, low-level delta TK RNA expression did not confer sensitivity to GCV. The uses of delta TK in cell-specific ablation in transgenic mice and in gene therapy are discussed.